AN ANALYSIS OF EDUCATIONAL VALUES OF THE NOVEL “ SILENT PATIENT ” BY ALEX MICHAELIDES - Dini Anggriani; Clarry Sada; Eni Rosnija (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
The low interest in reading in Indonesia threatens the quality of the young generation who hold Indonesia's future. Stimulating interest in reading can be done through reading materials that are popular among students, such as psychological thriller novels. Thus, researchers must encourage students to use English novels as reading material. This study aimed to determine the workability of the novel The Silent Patient by Alex Michaelides as reading material for EFL students. This study of "The Silent Patient" by Alex Michaelides used a qualitative descriptive research method. Moreover, the data collection technique used literature study techniques. The results of this study showed that from the reflection of educational values for EFL students in the following ways: first, the value of truth: mental, physical, and social well-being; second, the value of beauty in terms of creativity and uniqueness; third, religious values in terms of believing in God, believing in the hereafter; fourth, moral values in terms of always helping, perversion, and responsibility; The Silent Patient novel by Alex Michaelides is suitable as reading material for EFL students.